Main currents in Nigerian educational thought : Nnamdi Azikiwe, Obafemi Awolowo, Ahmadu Bello, Tai Solarin, Onyerisara Ukeje, Aliu Fafunwa, Jibril Aminu - Enoh, A. Owan (Jos, Nigeria : Midland Press, 1996)
From Nnamdi Azikiwe's education for human dignity and his philosophy of neo- welfarism and renascent Africa through Obafemi Awolowo's education for democratic empowerment and his mental magnitude and democratic socialism,to Ahmadu Bello's education for orderly change and his philosophy of realism and work and worship, from Tai Solarin's education for human freedom and his pragmatic and existentialist philosophies, to Onyerisara Ukeje's education for social recinstruction and his philosophy of social reconstructionism.
Includes bibliographical references (p. 363-398) and index.
aia 22/08/2016, ijb 06/02/2019
Loans
Keywords: Education; Education - Psychology; Educational thought; Nigeria